DEVELOPMENT OF ASSEMBLR EDU-ASSISTED AUGMENTED REALITY LEARNING MEDIA ON THE TOPIC OF EFFECT OF SURFACE AREA AND TEMPERATURE ON REACTION RATE - Briel Batis Tuta; Johnsen Harta; Sarah Sani Purwasih (Universitas Negeri Surabaya, 2022)
Understanding concepts at the submicroscopic and symbolic levels becomes challenge in studying subtopics of the effect of surface area and temperature because some parts are still abstract and difficult to understand. Creative and innovative learning media are needed to help learn concepts through visualization. This research aims to create product in the form of Augmented Reality assisted by Assemblr Edu that is valid, effective, and practical. This study is development research that adopts the modified Borg & Gall development model. The research subjects were 12 students of pre-service chemistry teachers. The research supporting instruments were validation sheets, test items, and response questionnaires. Data were analyzed using descriptive statistics and Aiken's V. The results showed that: (1) product fulfilled very valid criteria with average percentage of 91% with the results from the presentation and product use aspects of 90% (very valid), content aspect of 92% (very valid); language aspect by 92% (very valid); (2) the average test score of respondents after the trial is 75 which indicates that the results are good and the product is classified as effective; and (3) the average response to the product is 89% indicating that the product is very good and very practical for further use. This digital product is feasible to use and is recommended to support the understanding of the subtopic of the effect of surface area and temperature on the rate of chemical reactions.